Educação rural e desenvolvimento local sustentável: a lógica subjacente das relações inter-setoriais - OLIVEIRA, Lucia Marisy Souza Ribeiro de (2005)
This study aims to evaluate educational models generated inthe process of land occupation in the cities of Juazeiro, Uauá and Valente of the state of Bahia, not only in the irrigated areas but in dry land as well, having as guiding hypothesis the rural education as disseminating mechanism of information to the population and great mobilize of social, economic, politic, and cultural transformations of the communities, in the promotion of its sustainable development. The methodology of this research has taken as support the analysis of the social relation nets entwined in the process, choosing as categories preferences for the understanding of the phenomenon studied the social capital, local development, alternative pedagogy, school resume, and intersectorial partnership, through the splintering with the antagonism of the concepts of individual and society. It refers to a quanti-qualitative research founded in an approach of interactive character, where the speech emerges as space of negotiation of sense, and building of apprenticeship subject, whose subsidies added to the quantitative evidences allow the deepening of the complexity of the phenomena, its contradictions and relationship with the context. The analysis of data has conducted to understand that Rural Education in the areas researched live two situations: one, propagated for the public educational system which with the exception of some punctual experience do not care the interest of the people living and working in the field. The other, exercised by Non-Governmental Organizations which valuing the rural as space of life, form individuals with a repertoire of knowledge, abilities and values capable of mobilizing them in a transforming action.